La politique d'admission de la main-d'oeuvre étrangere: désirabilité, acceptabilité, intégrabilité - Weygold, Serge; Berset, Alain; Crevoisier, Olivier; Hainard, François (My University, 2001)
The reform of the Swiss policy of admission of foreign labour involves a discrimination in relation to professional skills, and no longer a geographical discrimination. This is, in particular, because the best qualified immigrants support the economic development of the country and are thought to have the strongest capacity for social integration. However, the article shows that: 1) to be highly qualified does not yet mean yet to be socially integrated; 2) the 'degree' of social integration of the immigrant workers depends on their migratory projects as well as their adaptation mode to the new work context, and not on a 'capacity' which they supposedly possess; 3) confusions which abound in the debate on this reform are due to the dominance of the 'integration' paradigm, to the detriment of the 'mobility' paradigm.
Keywords: Sociological research. Immigration. Immigration policy. Immigrants. Workers. Foreign workers. Social desirability. Social integration. Social acceptance.